2020
DOI: 10.1055/s-0040-1718952
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and Disadvantages of Medical Abortion, According to Brazilian Residents in Obstetrics and Gynaecology

Abstract: Objective To find out which was the opinion of residents in obstetrics and gynecology about the advantages and disadvantages of medical abortion as compared with surgical procedures. Method Cross-sectional multicenter study among residents in obstetrics and gynecology from 21 maternity hospitals located in 4 different geographical regions of Brazil, using a self-responded questionnaire with 31 questions related to their opinion and experience on providing abortion services. Results Most res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(33 reference statements)
0
0
0
Order By: Relevance
“…The obtained results may indicate a high level of empathy of the respondents. A study conducted in Brazilian students of medicine revealed that, in their opinion, abortion might prevent mental trauma [27]. The cited study emphasized the empathy of the students who focused on the feelings of women during the abortion procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained results may indicate a high level of empathy of the respondents. A study conducted in Brazilian students of medicine revealed that, in their opinion, abortion might prevent mental trauma [27]. The cited study emphasized the empathy of the students who focused on the feelings of women during the abortion procedures.…”
Section: Discussionmentioning
confidence: 99%
“…(5) No Brasil, o abortamento provocado ou induzido é proibido por lei, exceto nos casos em que há risco iminente de morte para a mulher, estupro ou anomalias congênitas. (6) O país possui um dos maiores índices de aborto ilegais do mundo, sendo mais ou menos 500.000 por ano entre mulheres de 18 a 39 anos, e por consequência cerca de 40 % ou 200.000 mulheres morrem por conta de suas complicações. (7) A Resolução do Conselho Federal de Enfermagem n.º 564/2017 (8) preconiza que é vetado a profissionais de Enfermagem provocar ou auxiliar em um processo de abortamento.…”
Section: Introductionunclassified